Respuesta :
Hi there!
[tex]3 - 5x + 6 = 14x - 32 + 10(2 - x)[/tex]
Work out the parenthesis.
[tex]3 - 5x + 6 = 14x - 32 + 20 - 10x[/tex]
Combine like terms.
[tex]9 - 5x = 4x - 12[/tex]
Subtract 9 from both sides.
[tex] - 5x = 4x - 21[/tex]
Subtract 4x from both sides
[tex] - 9x = - 21[/tex]
Divide both sides by -9
[tex]x = \frac{ - 21}{ - 9} = \frac{21}{9} = 2 \frac{3}{9} = 2 \frac{1}{3} [/tex]
[tex]3 - 5x + 6 = 14x - 32 + 10(2 - x)[/tex]
Work out the parenthesis.
[tex]3 - 5x + 6 = 14x - 32 + 20 - 10x[/tex]
Combine like terms.
[tex]9 - 5x = 4x - 12[/tex]
Subtract 9 from both sides.
[tex] - 5x = 4x - 21[/tex]
Subtract 4x from both sides
[tex] - 9x = - 21[/tex]
Divide both sides by -9
[tex]x = \frac{ - 21}{ - 9} = \frac{21}{9} = 2 \frac{3}{9} = 2 \frac{1}{3} [/tex]
3 - 5x + 6 = 14x - 32 + 10(2 - x)
Distribute 10 inside the parentheses.
3 - 5x + 6 = 14x - 32 + 20 - 10x
Combine like terms.
9 - 5x = 4x - 12
Add 5x to both sides.
9 = 9x - 12
Add 12 to both sides.
21 = 9x
Divide both sides by 9.
x = 21/9
Simplify 21/9 by dividing both sides by 3: 7/3
Your answer is x = 7/3.